Mission of Honour - Rovin, Jeff (London Penguin Books, 2002)
With intricate plotting, authenticity and suspense, this novel offers classic Tom Clancy. When Op-Centre are called upon to combat a new threat to the safety and security of the free world, international intrigue and exciting action are sure to follow.
Keywords: National Crisis Management Center (Imaginary place) -- Fiction